MEKANISME PENYELESAIAN PELANGGARAN KODE ETIK JURNALISTIK PADA DEWAN PERS DI KOTA SERANG - Sigit Surahman; Fuqoha Fuqoha (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2017)
Journalism is an activity of gathering news and reporting events. Delivery of news or information in general often also called the press. To protect journalistic activities and freedom of the press, the press council established by law. Press Council as an independent agency to establish guidelines which must be done by any reporter or journalist in writing or delivered the news. Journalistic ethics is a guideline to behave in journalistic activity compiled by journalists, press organizations to be ethical or moral grounding in journalistic activities. The purpose of this study, to find a model settlement of violations of journalistic ethics in the press council. This research method using descriptive analytical research model with normative juridical approach. Collecting data using literature study by collecting data and legal regulations. Besides the interviews to the parties concerned to complete the data. Press Council in resolving violations of journalistic ethics, to maintain the freedom of the press with a mechanism that provides power to the press council to decide a case arising from journalistic activities completed by the press council. Settlement due to journalistic activities outside the press council will shut down and eliminate the freedom of the press as mandated by law. The right model is the removal of press offenses perspective that may affect national press by giving power and authority to the press council to resolve matters arising from journalistic activities.